2001
DOI: 10.1530/eje.0.1450651
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-independent stimulation of activator protein-1 and c-Jun N-terminal kinase activity in human endometrial cancer cells by the LHRH agonist triptorelin

Abstract: Objective: The expression of luteinizing hormone-releasing hormone (LHRH) and its receptor as a part of an autocrine regulatory system of cell proliferation has been demonstrated in a number of human malignant tumours, including cancers of the endometrium. The signalling pathway through which LHRH acts in endometrial cancer is distinct from that in pituitary gonadotrophs. The LHRH receptor interacts with the mitogenic signal transduction of growth factor receptors via activation of a phosphotyrosine phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 49 publications
0
18
0
4
Order By: Relevance
“…AP1 motifs have been shown to be a converging site for several signal transduction pathways including ERK/MAP kinase, protein kinase C, and c-Jun N-terminal kinase pathways (22)(23)(24). In this study, we used TPA as a tool to explore the regulation of BCSG1 expression in breast cancer cells and we demonstrate that BCSG1 transcription was activated by TPA.…”
Section: Discussionmentioning
confidence: 91%
“…AP1 motifs have been shown to be a converging site for several signal transduction pathways including ERK/MAP kinase, protein kinase C, and c-Jun N-terminal kinase pathways (22)(23)(24). In this study, we used TPA as a tool to explore the regulation of BCSG1 expression in breast cancer cells and we demonstrate that BCSG1 transcription was activated by TPA.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, triptorelin activates c-Jun N-terminal kinase (JNK), which is known to activate AP-1 (102). In earlier investigations, we have shown that triptorelin does not activate PLC and PKC in endometrial and ovarian cancer cells (76).…”
Section: Additional Signaling Mechanismsmentioning
confidence: 98%
“…However, there is little evidence for PLC activation by endogenous extrapituitary LHRH-R-I (44,48). Instead, G i -mediated activation of protein phosphatase and inhibition of MAP kinase activity may be the basis of some of the antiproliferative effects mediated by LHRH-R-I (44,46,52,53). Investigation of the expression of extrapituitary LHRH-R-I revealed major functional differences between LHRH-R-I in human pituitary and extrapituitary sites, in spite of the expression of identical receptor transcripts (19).…”
Section: Discussionmentioning
confidence: 99%